Penerapan Metode Examples Non Examples Dalam Meningkatkan Hasil Belajar IPS di Kelas 5 SDN Cipanas Kota Sukabumi - Ridwan, Ridwan (utile: Jurnal Kependidikan, 2019)
Unoptimal students score average in social subject to reach 65 as minimum score is the reason for this research, especially in Indonesian Landscape subject. Conventional learning approach has conclude as one of many indicator that the students learning activity have not improve better and it cause learning result become unoptimal. The aims of the research are; 1) to describe social learning plan using Examples Non Examples method, 2) to describe social learning activities using using Examples Non Examples method, 3) to describe student learning result improvement in Cipanas Elementart School using Examples Non Examples method for social subject. This research approach through 3 (three) cycles of learning. The subjects of the research are 40 students of 4th grade Babakan Bandung Elementary School. The research conludes of 1st cycle that is students score average just reach 56.15. On 2nd cycle has rised to 62.00, then on 3rd cycle has rised significantly to 75.95. According to the score average result, Examples Non Examples Method implementation has able to improve the student’s score of social optimally.